Multiple Actions of 1S,3R-ACPD in Modulating Endogenous Synaptic Transmission to Spinal Respiratory Motoneurons - Dong, Xiao-Wei (J Neurosci, 1996)
To determine physiological roles of metabotropic glutamate receptors (mGluRs) affecting breathing, we examined the effects of (1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid (1S,3R-ACPD) on synaptic transmission and excitability of phrenic motoneurons (PMNs) in an in vitro neonatal rat brainstem/spinal cord preparation. The effects of 1S,3R-ACPD were multiple, including reduction of inspiratory-modulated synaptic currents and increase of neuronal excitability via an inward current (I(acpd)) associated with a decrease of membrane conductance. The mechanism underlying synaptic depression was examined. We found that 1S,3R-ACPD reduced the frequency but not the amplitude of miniature excitatory postsynaptic currents. The current induced by exogenous AMPA was not significantly affected by 1S,3R-ACPD. These results suggest that 1S,3R-ACPD-induced reduction of inspiratory synaptic currents is mediated by presynaptic mGluRs. We also examined the ionic basis forI(acpd). We found thatI(acpd) had a reversal potential of approximately −100 mV, close to the estimatedE(K(+)) (−95 mV). Elevating extracellular [K(+)] to 9 mm reduced the I(acpd)reversal potential to −75 mV. The K(+) channel blocker Ba(2+) induced an inward current with a reversal potential at −93 mV associated with a decrease of membrane conductance, closely resembling the effect of 1S,3R-ACPD. Moreover, Ba(2+) occluded 1S,3R-ACPD effects. In the presence of Ba(2+), I(acpd) and the 1S,3R-ACPD-induced decrease of membrane conductance were diminished. Our data indicate that the dominant component ofI(acpd) results from the blockade of a Ba(2+)-sensitive resting K(+)conductance. We conclude that the activation of mGluRs affects the inspiratory-modulated activity of PMNs via distinct mechanisms at pre- and postsynaptic sites.